Investigation of the effects of high cervical spinal cord electrical stimulation on improving neurological dysfunction and its potential mechanism in rats with traumatic brain injury. Issue 12 (5th July 2022) - Zhao, Peng-Cheng; Huang, Zhen-Shan; Xu, Shao-Nian; Deng, Peng-Cheng; Qian, Feng; Shi, Jian; Zhang, Yong-Ming
Abstract : To explore the effects of high cervical spinal cord electrical stimulation (cSCS) on the recovery of neurological function and its possible mechanism in rats with traumatic brain injury (TBI). 72 rats were randomly divided into: (1) a sham group; (2) a traumatic brain injury (TBI) group; (3) a TBI+cSCS group; (4) a LY294002+TBI+cSCS group. The degree of neurological dysfunction was evaluated by modified Neurological severity score (mNSS). The pathological changes of the brain tissue in the injured area were observed by HE staining, and the apoptosis of neuron cells were observed by TUNEL staining. The expressions of BDNF and VEGFmRNA were detected by polymerase chain reaction (PCR), and the expressions of p-AKT, AKT, Bcl-2, Bax and caspase-3 proteins were detected by western blot. Compared with that of the TBI and LY294002+TBI+cSCS groups, the mNSS of the TBI+cSCS group were significantly lower on day 3 and 7 ( P <0.05). Compared with that in the TBI and LY294002+TBI+cSCS groups, the apoptosis of neuron cells in the TBI+cSCS group decreased significantly ( P < 0.05). Compared with the TBI and LY294002+TBI+cSCS group, the expression of Bcl-2 protein increased and the expressions of Bax and Caspase-3 proteins decreased in the TBI+cSCS group ( P < 0.05). Compared with that in the TBI and LY294002+TBI+cSCS groups, the intensity of p-Akt/Akt in the TBI+cSCS group increased ( P < 0.05). We found that cSCS had a protective effect on neuron cells after craniocerebral injury and could improve neurological dysfunction in rats, the mechanism of which might be that cSCS made the PI3K/Akt pathway more active after TBI.